Propuesta de Mejora del Sistema de Gestión de Mantenimiento en la Empresa Transportliquidos S.A.S - Pascuales Figueroa, Sasha Marcela; Pedraza Quiroga, Astrid Katherine (Universidad Antonio Nariño, 2022)
Given the current competitive scenario, global business trends recognize innovation and creativity as fundamental elements to stay afloat; however, the companies in the transforming link of the Colombian dairy sector require more work in innovation and creativity.